Kinesiotherapy in women after gynecological surgeries - Majchrzycki, Marian; Seremak-Mrozikiewicz, Agnieszka; Kulczyk, Aleksandra; Lipiec, Joanna (Menopause Review/Przegląd Menopauzalny, 2012)
Patients after abdominal surgeries require comprehensive medical care, which includes the rehabilitation of motor organs. It also applies to women after gynaecological procedures. Proper physiotherapy adapted to a specific procedure is of great importance. The purpose of the paper is to present comprehensive physiotherapy of female patients after gynaecological surgeries. Physiotherapeutic procedures restore motion ability, increase muscle strength, restore proper joint motion, leading to reduced inflammation and faster wound healing. Abdominal surgeries can result in a large number of possible complications, including complications in the respiratory and urinary system (stress urinary incontinence) and in the musculoskeletal system (body posture disorders, myofascial disorder caused by tissue scarring). The paper discusses the rehabilitation of patients in the pre-surgery period, early post-surgery period and in outpatient therapy as well as scar tissue massage.